Classical and modern concepts of corporate governance (Stewardship Theory and Agency Theory) - Glinkowska Beata; Kaczmarek Bogusław (Management)
The main issues in efficiency of a company as an organisation are relations between the Supervisory Board and the Management Board of a company, and the methods of functioning of Supervisory Boards in governance systems of a company.